2018
DOI: 10.1111/andr.12514
|View full text |Cite
|
Sign up to set email alerts
|

The achievement of boar spermin vitrocapacitation is related to an increase of disrupted disulphide bonds and intracellular reactive oxygen species levels

Abstract: The aim of this work was to determine the relationship of intracellular reactive oxygen species (ROS) and the disulphide bonds established between sperm proteins with the achievement of capacitation in boar spermatozoa. With this purpose, spermatozoa were incubated in a specifically designed in vitro capacitation medium (CM) in the presence or absence of reduced glutathione (GSH). Incubation of boar spermatozoa in CM for 4 h significantly (p < 0.05) increased free cysteine residues, which is a marker of disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…However, only a few studies have investigated the effect of sperm capacitation on the chromatin structure. These studies found that spermatozoa showed a less compacted chromatin, sperm DNA integrity remained unchanged and the disulphide bonds between protamines decreased during in vitro capacitation 21‐24,46‐48 . Nevertheless, to the best of our knowledge, no previous studies have investigated sperm DNA methylation during this event.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, only a few studies have investigated the effect of sperm capacitation on the chromatin structure. These studies found that spermatozoa showed a less compacted chromatin, sperm DNA integrity remained unchanged and the disulphide bonds between protamines decreased during in vitro capacitation 21‐24,46‐48 . Nevertheless, to the best of our knowledge, no previous studies have investigated sperm DNA methylation during this event.…”
Section: Discussionmentioning
confidence: 96%
“…These studies found that spermatozoa showed a less compacted chromatin, sperm DNA integrity remained unchanged and the disulphide bonds between protamines decreased during in vitro capacitation. [21][22][23][24][46][47][48] Sperm chromatin condensation can be evaluated rapidly with aniline blue (AB). This cytochemical dye selectively stains persisting lysine-rich histones 49,50 and has been widely used to identify an excessive histone retention in the chromatin of mature spermatozoa, which has been related to infertility, poor fertilization rates and morphological defects in the sperm head.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being mature and motile once ejaculated, mammalian sperm must reside in the female reproductive tract to acquire their fertilizing ability, in a process known as capacitation [ 1 , 2 , 3 ]. During capacitation, sperm undergo an assortment of physiological and biochemical changes, including alterations in plasma membrane permeability and fluidity [ 4 , 5 ], acrosome integrity [ 6 ], intracellular pH and calcium levels [ 7 , 8 ], mitochondrial activity [ 9 ], and the generation of reactive oxygen species (ROS) [ 10 ]. Oxidative stress, caused by excessive ROS formation, has detrimental consequences for sperm cells and fertility, including a decrease in sperm motility and their ability to interact with the oocyte, an increase in plasma membrane lipid peroxidation, protein damage and DNA fragmentation, and even the activation of apoptotic-like pathways [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress, caused by excessive ROS formation, has detrimental consequences for sperm cells and fertility, including a decrease in sperm motility and their ability to interact with the oocyte, an increase in plasma membrane lipid peroxidation, protein damage and DNA fragmentation, and even the activation of apoptotic-like pathways [ 11 ]. Notwithstanding, moderate levels of ROS are needed to perform some physiological processes, such as sperm capacitation [ 10 , 12 ]. Indeed, ROS generation during early capacitation events induces a rise of cAMP levels and the activation of protein kinases, which, in turn, trigger the phosphorylation of tyrosine residues of certain proteins, stimulating specific downstream pathways [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%